Porcine Protein Hydrolysates (Pepteiva®) Promote Growth and Enhance Systemic Immunity in Gilthead Sea Bream (Sparus Aurata) - Reyes-Lopez, F; Vallejos-Vidal, E (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The effects of porcine plasma protein hydrolysate (PPH) on growth, feed efficiency, and immune responses was evaluated in Sparus aurata. Fish were fed two isoproteic (48% protein), isolipidic (17% fat), and isoenergetic diets (21.7 MJ/kg) diets, one of them containing 5% PPH at the expense of fishmeal. Both diets were tested for 92 days. A significant increase in growth was observed in fish fed the PPH diet in comparison to the control group (182.2 ± 4.4 vs. 173.8 ± 4.1 g), as well as an increase in feed intake without worsening FCR values. An ex vivo assay, with splenocytes incubated with lipopolysaccharide, was conducted to evaluate the cellular immune competence of fish. Genes involved in humoral immunity (lys, IgM), pro-(tnf-α, il-1β), and anti-inflammatory (tgf-β1, il10) cytokines were upregulated in the PPH group in comparison to the control group. The inclusion of PPH in diets enhanced the antibacterial capacity of skin mucus, as the co-culture of selected bacteria (E. coli, V. anguillarum and P. anguilliseptica) with skin mucus indicated. The present results showed that the PPH in low fishmeal diets (2%) promoted growth and feed efficiency, as well as enhancing the immune response, which indicates that this is a safe and functional ingredient for aquafeeds. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: aquaculture; functional feed; protein hydrolysates; low fishmeal diet; pathogen-associated molecular pattern (PAMP); skin-associated lymphoid tissue (SALT)